2023
DOI: 10.3390/plants12061389
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding of Multiple Genes to Improve Rice Blast Resistance of Photo-Thermo Sensitive Male Sterile Line, without Yield Penalty in Hybrid Rice Production

Abstract: Rice blast caused by pathogenic fungus Magnaporthe oryzae is one of the most serious diseases in rice. The pyramiding of effective resistance genes into rice varieties is a potential approach to reduce the damage of blast disease. In this study, combinations of three resistance genes, Pigm, Pi48 and Pi49, were introduced into a thermo-sensitive genic male sterile (PTGMS) line Chuang5S through marker-assisted selection. The results showed that the blast resistance of improved lines increased significantly compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…MAS analysis facilitates the identification of genes, their introduction and pyramiding into new lines [40,41], that significantly speeds up rice breeding. The combination of several genes in one genotype showed the greatest effect, indicating the effectiveness of the strategy of durable rice resistance to blast [7][8][9][10][11][12][13][14]35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAS analysis facilitates the identification of genes, their introduction and pyramiding into new lines [40,41], that significantly speeds up rice breeding. The combination of several genes in one genotype showed the greatest effect, indicating the effectiveness of the strategy of durable rice resistance to blast [7][8][9][10][11][12][13][14]35].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of several genes in one genotype showed the greatest effect, indicating the effectiveness of the strategy of durable rice resistance to blast [7][8][9][10][11][12][13][14]35]. Rice lines carrying both individual resistance genes [40,42] and lines with pyramided genes (containing combinations genes) with a broad spectrum of resistance to Magnaporthe oryzae were created [41,43]. Thus, as a result of molecular screening of parental samples for the presence of genes, it was shown that the resistance of local zoned rice cultivars Bakanasski, Fatima, Aisaule and Aru, out of the four genes studied, only one gene Pi-2 is present and only in the cultivars Bakanasski, Aisaule and Aru.…”
Section: Discussionmentioning
confidence: 99%